Analysis of Moral Values in the Song of Onogu Omasiö by Daniel Folala Zalukhu - Gea, Boy Berkat Iman; Mastawati Ndruru; Lestari Waruwu; Iman Sudi Zega (Universitas Negeri Semarang, 2024)
This research aims to describe the moral values in the song